2000
DOI: 10.1016/s0378-4274(00)00267-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of mice to tobacco smoke attenuates the toxic effect of methamphetamine on dopamine systems

Abstract: SUMMARY 231The mechanisms underlying the toxicity of ethanol have been the subject of much study, but are not well understood. Unlike many selective pharmacological agents, ethanol clearly has several major loci of action. One deleterious factor in ethanol metabolism is the potential for generation of excess amounts of free radicals. The extent to which this activity accounts for the overall toxicity of ethanol is unknown. This review outlines the enzymic steps that have the capacity to generate reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…NIC also appears to have a protective effect against MA-induced DA neurotoxicity in adult rodents. For example, adult MA-exposed male mice exhibit reductions in striatal DA levels to 18% of controls, while mice exposed to NIC prior to MA show striatal DA levels measuring 57% of controls [24]. NIC prevents MA-induced striatal DA depletion [25] and MA-induced DA terminal neurodegeneration [26] in adult male mice and in adult rats, NIC pre-treatment reduces MA self-administration [27].…”
Section: Introductionmentioning
confidence: 99%
“…NIC also appears to have a protective effect against MA-induced DA neurotoxicity in adult rodents. For example, adult MA-exposed male mice exhibit reductions in striatal DA levels to 18% of controls, while mice exposed to NIC prior to MA show striatal DA levels measuring 57% of controls [24]. NIC prevents MA-induced striatal DA depletion [25] and MA-induced DA terminal neurodegeneration [26] in adult male mice and in adult rats, NIC pre-treatment reduces MA self-administration [27].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of post-mortem brain tissue from methamphetamine users showed a significant decrease in dopamine content and dopamine transporter (DAT) density [19]. Methamphetamine has been shown to induce striatal dopamine depletion in mice striatum, hence it can be ideal to study the disease progression and for evaluating neuroprotective drugs [12,20]. It has been further shown that repeated administration of methamphetamine reduces DAT binding and causes persistent dopaminergic depletion in the striatum [7,17,18].…”
Section: Introductionmentioning
confidence: 99%